If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+7(x-9)=69
We simplify the equation to the form, which is simple to understand
4x+7(x-9)=69
Reorder the terms in parentheses
4x+(+7x-63)=69
Remove unnecessary parentheses
+4x+7x-63=+69
We move all terms containing x to the left and all other terms to the right.
+4x+7x=+69+63
We simplify left and right side of the equation.
+11x=+132
We divide both sides of the equation by 11 to get x.
x=12
| x+0.07x=282.68 | | -14-4r=-2+8r | | 6x+y=27 | | 7k+8+8k=11+5+4k+3k | | 5y-3y=27 | | 3x+7(5x-5)=193 | | 2t+-1=3t+7 | | 3b-5=-7+2b | | 5x+4y=63 | | 4f+x-4=-4 | | 18=-4x-5x | | 5x+6(3x-15)=117 | | 2x+2(2x+5)=250 | | 3x+5(0)=30 | | -x=15+30 | | -6=-4p+5p | | 1.50x+0.75=2.00x+0.50 | | 3x+5(-3)=30 | | -15=4b-b | | 1/2x^2=8x−5/8 | | 3x+2(2x+5)=45 | | 3/4*4/5 | | 6-0.5u=11-1.33u | | 3(-5)+5y=30 | | -12=a+6+5a | | log(x)+log(x-15)=2 | | 5x+20=10(x+2)-5x | | 10x-8=136 | | -10=6n-1-3 | | 4x+6(2x+4)=104 | | -7=7*-1 | | -4n+6n=8 |